Kinematic analysis of javelin throw performed by wheelchair athletes of different functional classes - Chow, J. W.; Kuenster, A. F.; Lim, Y.-T. (Journal of Sports Science & Medicine, 2003)
The purpose of this study was to identify those kinematic characteristics that are most closely related to the functional classification of a wheelchair athlete and measured distance of a javelin throw. Two S-VHS camcorders (60 field·s(-1)) were used to record the performance of 15 males of different classes. Each subject performed 6-10 throws and the best two legal throws from each subject were selected for analysis. Three-dimensional kinematics of the javelin and upper body segments at the instant of release and during the throw (delivery) were determined. The selection of kinematic parameters that were analyzed in this study was based on a javelin throw model showing the factors that determine the measured distance of a throw. The average of two throws for each subject was used to compute Spearman rank correlation coefficients between selected parameters and measured distance, and between selected parameters and the functional classification. The speeds and angles of the javelin at release, ranged from 9.1 to 14.7 m·s(-1) and 29.6 to 35.8°, respectively, were smaller than those exhibited by elite male able-bodied throwers. As expected, the speed of the javelin at release was significantly correlated to both the classification (p<0.01) and measured distance (p<0.001). Of the segmental kinematic parameters, significant correlations were found between the trunk inclination at release and classification and between the angular speed at release and measured distance (p<0.01 for both). The angular speed of the shoulder girdle at release and the average angular speeds of the shoulder girdle during the delivery were significantly correlated to both the classification and measured distance (p<0.05). The results indicate that shoulder girdle movement during the delivery is an important determinant of classification and measured distance.